2009
DOI: 10.2495/air090321
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of atmospheric toxic pollutants over Cairo, Egypt

Abstract: This paper discusses import of physical ideas on management and human response to Air Pollution (AP). It looks into some historical, evolutionary, ecological and philosophical aspects of AP. Paper emphasizes a need for more extended philosophical reflections on AP which should go beyond mere technical issues of monitoring and control. Keywords: air pollution, biosphere, evolution, adaptation, hormesis, quantum physics, chaos, ecology, singularity theory, management of air pollution, fuzzy logic, random models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…In an Egyptian study, Hassanien [6] had assessed human health risk estimates derived from potential metal inhalation of urban inhabitants by estimation of the distribution of toxic pollutants including primarily that of great risk for human health in atmospheric air samples collected from different regions in Cairo, Egypt. It was concluded that, the current levels of metals in air including cadmium were higher than those considered safe for the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an Egyptian study, Hassanien [6] had assessed human health risk estimates derived from potential metal inhalation of urban inhabitants by estimation of the distribution of toxic pollutants including primarily that of great risk for human health in atmospheric air samples collected from different regions in Cairo, Egypt. It was concluded that, the current levels of metals in air including cadmium were higher than those considered safe for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, closed Manzallah Lake is seriously contaminated with heavy metals including cadmium, as a result of increasing discharge of untreated industrial wastes as well as agricultural irrigation by wastewater [5]. Hassanien [6] assessed human health risk estimates in residents from different regions in Cairo, Egypt. He concluded that, the current levels of copper, chromium, cadmium, lead, manganese, vanadium, arsenic, nickel, antimony and titanium were higher than those considered safe for the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Closed Manzallah Lake in Dakahlia governorate is contaminated with heavy metals including cadmium, due to increased discharge of untreated industrial wastes and agricultural irrigation by wastewater (14). Hassanien assessed human health risk estimates in residents from different regions in Cairo, Egypt (15). He concluded that, the current levels of copper, chromium, cadmium, lead, manganese, vanadium, arsenic, nickel, antimony and titanium were higher than those considered safe for the general population.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Owing to the fact that tyres contain many potentially harmful substances: natural and synthetic rubber polymers, oil fillers, sulfur and sulfur compounds, phenolic resin, clay, aromatic, naphthenic and paraffinic oil, fabric, petroleum waxes, pigments such as zinc oxide and titanium dioxide, carbon black, fatty acids, inert materials and fibres made from steel, nylon, polyester or rayon [3][4][5][6][7][8][9] , singeing Kanda with scrap tyres may impose the risk of depositing these elements and compounds into the kanda, and expose the unsuspecting consumer to health hazards. It is on this premise that this study investigates the effects of consuming scrap tyre and firewood singed cattle hides on the vital organs (kidney, liver and heart) of Wistar rats.…”
Section: Yesmentioning
confidence: 99%